Estudo do emprego de broca especial em substituição ao alargador na produção de furos em ferro fundido vermicular - Reis, Alcione dos (2014)
In many applications of metalworking industry it is required mass production of parts containing holes with finish and tolerances typically from precision assembling, with working quality, ISO IT grade, ranging from IT7- IT5. But to produce these holes with tighter tolerances and with low geometrical errors, conventional twist drills may be not enough, so further processes are required, like reaming for example. Before any reaming process comes the drilling process, resulting in two different tools, two parts on necessary machining time, which in turn affects productivity and competitiveness. Therefore , any investment in the production of tools and techniques to reduce the machining time of close tolerance holes without affecting the integrity of the surface and preferably at a lower cost , will receive special attention from the machining community. In this context, this paper presents a technical and economic study of the use of special designed drill in replacement by a reamer the production of cylindrical holes of 10 mm diameter pieces of compacted graphite cast iron in terms of finish, roundness and dimensional deviation. It was also investigated the influence of the allowance in the final quality of the machined hole reamer. The surface of the holes and the microhardness of the machined holes were also analyzed and the tool wear was monitored. Finally, the economic analysis of the tools employed was performed. The results showed that special drill resulted in finish and dimensional deviation as good as those produced by the reamer. IT6 was the working quality obtained after reaming with reaming allowance of 0.5mm, while IT8 quality was obtained by using the special designed drill. Wear on special drill was lower than that observed in the reamer, and for the latter chipping occurred. Up to 29% of reduction in machining time was achieved by using the special drill, which resulted in a reduction of 33% cost as well. In contrast the values of cylindricity deviations were higher than those obtained with the reamers under the conditions investigated. The hardness was not affected by the processes employed.